2022
DOI: 10.1038/s41598-022-21973-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two QTLs, BPH41 and BPH42, and their respective gene candidates for brown planthopper resistance in rice

Abstract: The brown planthopper (BPH) is the leading cause of insect damage to rice plants and BPH infestations have caused profound losses in rice production since the 1970’s. There is an urgent need to discover new BPH resistance genes to ensure the successful production of rice. Here, a new BPH resistance source provided by SeedWorks International Pvt. Ltd., SWD10, was used for this purpose. QTL mapping using 232 F2 progenies and 216 polymorphic markers revealed two dominant BPH resistance QTLs, BPH41 and BPH42, loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…For example, Yang et al (2019) [65] have positioned Bph37 between RM302 and YM35 in chromosome 1 in IR64, while Zhou et al (2021) [66] has cloned a resistance gene on chromosome 6 in SE382 and also named it Bph37. Similarly, Tan et al (2022) [69] have located the resistance gene Bph41 between SWRm_01617 and SWRm_01522 in chromosome 4, and in the same year, Wang et al (2022) [70] have reported Bph41, locating it between the molecular markers W4-4-3 and W1-6-3 on chromosome 4. As a result, the nomenclature of BPH-resistant genes has become confusing.…”
Section: Discussionmentioning
confidence: 92%
“…For example, Yang et al (2019) [65] have positioned Bph37 between RM302 and YM35 in chromosome 1 in IR64, while Zhou et al (2021) [66] has cloned a resistance gene on chromosome 6 in SE382 and also named it Bph37. Similarly, Tan et al (2022) [69] have located the resistance gene Bph41 between SWRm_01617 and SWRm_01522 in chromosome 4, and in the same year, Wang et al (2022) [70] have reported Bph41, locating it between the molecular markers W4-4-3 and W1-6-3 on chromosome 4. As a result, the nomenclature of BPH-resistant genes has become confusing.…”
Section: Discussionmentioning
confidence: 92%
“…Three genes (bph11, qBph3, and Bph14) were clustered between 35.60 and 35.80 Mb of chromosome 3L [29,32,34]. A total of 21 genes were located on chromosome 4: five genes (Bph44(t), qBph4.3, Bph33, Bph30, and Bph41) were clustered between 0.17 and 1.10 Mb on chromosome 4S [2,24,[35][36][37]; 11 genes (Bph40, Bph12, qBph4.1, Bph3, Bph35, qBph4.2, Bph15, Bph36, qBph4, Bph20(t), and Bph17) were clustered between 4.44 and 9.38 Mb on chromosome 4S [2,3,33,[38][39][40][41][42][43][44]; and Bph27(t), Bph6, Bph44, Bph34, and Bph42 were clustered on chromosome 4L between 20.60 and 21.80 Mb [24,37,[45][46][47]. The Bph37 that from SE382, Bph25, bph29, Bph32 and bph4 were present on chromosome 6S between 0.21 and 1.47 Mb [22,[48][49][50][51].…”
Section: Bph-resistance Gene Mappingmentioning
confidence: 99%
“…4.44 and 9.38 Mb on chromosome 4S [2,3,33,[38][39][40][41][42][43][44]; and Bph27(t), Bph6, Bph44, Bph34, and Bph42 were clustered on chromosome 4L between 20.60 and 21.80 Mb [24,37,[45][46][47]. The Bph37 that from SE382, Bph25, bph29, Bph32 and bph4 were present on chromosome 6S between 0.21 and 1.47 Mb [22,[48][49][50][51].…”
Section: Bph-resistance Gene Mappingmentioning
confidence: 99%
“…Genetic analysis led to the identification of 70 genes and a quantitative trait locus (QTL) associated with BPH resistance in rice. However, efficient utilization of these markers required gene/QTL duplication in as many as 26 known cases [31][32][33][34]. The insights from this review could advance the development of sustainable biological control strategies for managing BPH infestations.…”
mentioning
confidence: 99%